2004
DOI: 10.1007/s15010-004-3089-x
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Disease Pattern and Disease Burden by Chest Radiography, M. tuberculosis Load, and HIV Status in Patients with Pulmonary Tuberculosis in Addis Ababa

Abstract: CXR findings in the setting of an underlying HIV infection tend to be more atypical and could present as either normal or with minimal involvement. In general, HIV-positive patients had lower colony count of M. tuberculosis than HIV-negative patients. Of particular interest is the finding of a large number of normal chest X-rays in HIV-infected patients. With the rising incidence of both tuberculosis and HIV infection in Ethiopia, the finding of a normal chest X-ray and a negative smear poses a challenge for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
23
2
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 19 publications
5
23
2
1
Order By: Relevance
“…[34] Unfavourable outcomes in co-infected patients may be due to a delay in diagnosis because of atypical clinical presentation, and it is also known that co-infected patients tend to have paucibacillary TB or low microbacterial colony counts. [35] This reduction in microbacterial count makes the diagnosis of TB by smear microscopy more difficult.…”
Section: Researchmentioning
confidence: 99%
“…[34] Unfavourable outcomes in co-infected patients may be due to a delay in diagnosis because of atypical clinical presentation, and it is also known that co-infected patients tend to have paucibacillary TB or low microbacterial colony counts. [35] This reduction in microbacterial count makes the diagnosis of TB by smear microscopy more difficult.…”
Section: Researchmentioning
confidence: 99%
“…Wide variations have been observed on chest radiography among HIV patients. A study in Senegal has reported that such patients present with atypical chest radiographs, and could also present with normal or minimal chest lesions (Aderaye et al, 2004). The variability could be due to differing CD4 levels among these HIV TB co-infected patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, the XpertMTB/RIF performance in active case detection among HIV positive TB patients has not been evaluated in Tanzania. The HIV infected patients tend to have atypical and/or asymptomatic TB leading to difficult and delayed diagnosis when using microscopy, and hence increased rates of morbidity and mortality (Aderaye et al, 2004). In this study, we evaluated the performance and effectiveness of XpertMTB/RIF, compared to microscopy, in TB detection among HIV positive patients using Lowenstein-Jensen culture as a gold standard.…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, the reported rates of normal chest X-rays in patients with smear-or culture-positive PTB are low, (4,11,13,22,24) except in HIV-infected patients. (8) A prevalence survey conducted in Cape Town, South Africa revealed that the presence of any abnormalities on chest X-ray has a high sensitivity for detecting subjects with smear-or culture-positive tuberculosis (0.97%; 95% CI: 0.90-1.00). (26) In our sample of 800 male patients, there was only one case of smear-or culture-positive tuberculosis and a normal chest X-ray.…”
Section: Discussionmentioning
confidence: 99%
“…The lesions are typically seen in the apical and posterior segments of the upper lobes, as well as in the superior segments of the inferior lobes. (2)(3)(4)(5)(6)(7)(8) However, in patients with HIV infection, diabetes, silicosis or malignancy, especially in females and in the elderly, the lower lung fields can be involved. (2,4,7,(9)(10)(11)(12)(13) Although sputum smear and culture are the main tools for the diagnosis and follow-up of PTB, clinicians frequently use chest X-ray in the differential diagnosis and the assessment of treatment responses.…”
Section: Introductionmentioning
confidence: 99%